KENANGA: WOMEN’S CULTURE (AN ANALYSIS OF NOVEL, A WORK OF FEMALE AUTHOR WITH PRESPECTIVE ELAINE SHOWALTER CULTURE MODEL) - Yessy Hermawati (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
In understanding the women’s culture, historians see and distinguish various aspects of identity, roles, relationships, attitudes and pictures of women's lives formed in the culture of society in general. Female writers also express and present the women’s culture in their works. This study discusses how the women’s culture is represented in a novel written by a woman. A work that is written with attention to the cultural elements of women that presents women's lives through experience and narration. The object analyzed in this study is Oka Rusmini's novel entitled "Kenanga" which tells the women’s lives with Balinese cultural background. Oka Rusmini, the author is also a Balinese woman. The novel is analyzed by using the approach of Subjectivity (Spivak,1994) and Elaine Showalter cultural model (Showalter,1982) especially women's writing and women's culture model. This study shows that women authors represent experiences and women's issues in their works. Women authors also write down their responses and perspectives on the patriarchal culture that surrounds their lives with a Balinese cultural setting. Oka Rusmini also conveys resistance of social and cultural constructions which make women become subordinate through the attitude and life of the characters in her novel.